Analysis of left ventricular hypertrophy predictors in women with different levels of obesity - Anna Viktorovna Postoeva; Irina Vladimirovna Dvoryashina; Zoya Enverovna Bakhtina; Irina Vladimirovna Eliseeva (Ожирение и метаболизм, 2015)
Introduction. Previous studies have shown that patients with obesity had left ventricular hypertrophy (LVH) in 27–69,4% cases along with normal geometry of left ventricle (LV).Aim. To investigate new possible clinical and hormonal predictors of LVH in women with obesity of different degrees.Materials and methods. We conducted trans-sectional study in women with obesity, we performed clinical examination and echocardiography with calculation of mass of myocardium of LV (MMLV), indexed MMLV (IMMLV) to body surface area and relative wall thickness (RWT). LVH was diagnosed at IMMLV≥95 g/m2, increase of RWT when RWT≥0.42. Blood levels of fasting insulin, leptin and adiponectin were investigated. Differences between groups were assessed with Student’s t-test for independent samples, U-criterion of Mann-Whitney and Chi-square test (χ2). Correlation was estimated with Spearman's coefficient (rs). Multiple and logistic regression analyses were performed for detection of predictors. Statistics were performed with SPSS (version 13.0), differences were significant at level p<0.05.Results. We assessed the results in 113 women (age 44.34±11.18 years, body mass index 35.0±5.3 kg/m2). Total 67 women were diagnosed with LVH (59.3%), 56.5% among them had arterial hypertension (AH). Increase of RWT was revealed in 25 participants (22.1%), 80% of them had arterial hypertension (AH). Levels of fasting leptin, insulin and adiponectin did not differ in groups of women with or without LVH, with or without increase of RWT. In multiple regression age (β=1.67, p=0,005), body mass (BM) (β=2.63, p=0.004) and mean blood pressure (BP) (β=1.07, p=0.009) were independent predictors of MMLV increase; age (β=0.83, p=0.006) and mean BP (β=0.56 p=0.007) – predictors of IMMLV increase. In logistic regression age (odds ratio (OR)=1.058, p=0.036) and BM (OR=1.065, p=0.05) were independent predictors of LVH; presence of AH (OR=4.011, p=0.05) and level of adiponectin (OR=2.618, p=0.048) – predictors of RWT increase.Conclusions. Women with obesity with or without AH had LVH in 59.3% cases. Age and BM were independent positive predictors of LVH, presence of AH and adiponectin – independent positive predictors of increase of RWT of LV.